2022
DOI: 10.1088/1361-6420/ac28ec
|View full text |Cite
|
Sign up to set email alerts
|

Task adapted reconstruction for inverse problems

Abstract: The paper considers the problem of performing a post-processing task defined on a model parameter that is only observed indirectly through noisy data in an ill-posed inverse problem. A key aspect is to formalize the steps of reconstruction and post-processing as appropriate estimators (non-randomized decision rules) in statistical estimation problems. The implementation makes use of (deep) neural networks to provide a differentiable parametrization of the family of estimators for both steps. These networks are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…A proof-of-concept study regarding this was given by [80], where we showed that an image abnormality detection task may induce a significantly different image quality metric from pixel-level metric. Works in computer vision [42,41] and radiology [34] also suggest potentials of task-driven imaging, and a theoretical framework was introduced by [2]. Therefore, the unification may lead to more effective and practically relevant ways to evaluating imaging qualities and more economic sensing strategies for a given task or a set of tasks.…”
Section: Task-driven Computational Imagingmentioning
confidence: 99%
“…A proof-of-concept study regarding this was given by [80], where we showed that an image abnormality detection task may induce a significantly different image quality metric from pixel-level metric. Works in computer vision [42,41] and radiology [34] also suggest potentials of task-driven imaging, and a theoretical framework was introduced by [2]. Therefore, the unification may lead to more effective and practically relevant ways to evaluating imaging qualities and more economic sensing strategies for a given task or a set of tasks.…”
Section: Task-driven Computational Imagingmentioning
confidence: 99%
“…This propagated wavefront set, along with the characterisation of the visible wavefront set, is used for setting up the DNN for wavefront set inpainting, which recovers the invisible part of the wavefront set of a signal from the visible part. This DNN for wavefront set inpainting is then combined with the Learned Primal-Dual network for reconstruction, and both DNNs are trained jointly following the task-adapted reconstruction paradigm outlined in [1], see Section 5.6 for further details.…”
Section: Outline Of the Papermentioning
confidence: 99%
“…where C ∈ (0, 1] and 1 , 2 are appropriate distance measures on discretised images and discretised wavefront sets that will be discussed in Subsection 3.4 below. This strategy that jointly trains a reconstruction and a task (wavefront set inpainting) falls in the framework of task-adapted reconstruction was introduced in [1].…”
Section: Outline Of Our Algorithmmentioning
confidence: 99%
“…For instance, in medical imaging the CT image might be used for identification and quantification of cancer tissue [11]. Thus, in recent years some researchers have also increasingly considered to combine both tasks in a joint framework [12], [13], [14]. Nevertheless, we will concentrate here on a separated approach, but keep the segmentation quality in mind as evaluation criterion of reconstruction quality rather than quantitative reconstruction errors.…”
Section: Introductionmentioning
confidence: 99%